CLINICAL CASE OF METHYLMALONIC ACIDEMIA - Elena Anatolyevna Tkachuk; Darya Mikhailovna Barykova; Yuliya Sergeevna Livadarova; Igor Zhanovich Seminsky; Tatyana Alexandrovna Astakhova; Elena Gennadievna Osipova; Yuliya Viktorovna Mikhelsone; Tatyana Yuryevna Dorofeeva; Nikolay Vasilyevich Syrkin; Maria Igorevna Krasnova; Anna Viktorovna Rudakova; Daria Yuryevna Alexandrova (Байкальский медицинский журнал, 2023)
The paper describes a clinical case of methylmalonic acidemia in a newborn premature baby with a aggravated genealogical and obstetric history. The problems of diagnosing aminoacidopathy as a large heterogeneous group of hereditary diseases, which, as a rule, manifest in early childhood and are accompanied by life-threatening or disabling consequences, are considered. The paper presents clinical and laboratory data on methylmalonic acidemia, and analyzes the mechanisms of pathogenesis. It is noted that the difficulty in diagnosing methylmalonic acidemia, as well as other aminoacidopathy, is associated with the polymorphism of the clinical picture, the absence of specific clinical manifestations at the onset of the disease manifestation, and the use of special research methods in the diagnosis. It has been shown that the presence of aggravated factors often does not allow correct interpretation of clinical and laboratory data, making timely diagnosis and treatment difficult. Conclusion. Diagnosis of methylmalonic adiduria should take into account the unfolding of metabolic changes in the blood and urine over time. It is necessary to simultaneously analyze changes in the levels of metabolites in the blood and urine. The gold standard and the most reliable method of delivering a diagnosis is DNA diagnostics.